Estudo do carcinoma espinocelular cutâneo em gatos: Avaliação dos aspectos clínicos e histopatológicos e associação com a imunoexpressão de COX-2 - Isabella Oliveira Almeida (2023)
Cutaneous squamous cell carcinoma (CSCC) stands out among malignant cutaneous neoplasms in cats, having similarities to “non-melanoma” skin cancer in humans, such as the etiopathogenesis related to exposure to ultraviolet radiation, anatomical location predominantly on the face and biological behavior with high local aggressiveness, however, with low metastatic potential. This study aimed to evaluate the expression of COX-2 in CSCC in domestic cats and to evaluate the correlation with clinical and histopathological aspects. Cats attended at the Veterinary Hospital of the Veterinary School of the Federal University of Minas Gerais, with skin lesions suspicious for invasive squamous cell carcinoma, were included. The medical records were retrieved to record the breed, age, sex, location of the lesions, treatment performed, clinical staging, status of the feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV) immunochromatographic test, time of disease progression, history of recurrence, and survival. Subsequently, histological sections were performed and classification into atypical epithelial hyperplasia, actinic keratosis, carcinoma in situ or invasive squamous cell carcinoma well, moderately or poorly differentiated and Nagamine grading for CSCC evaluating: degree of keratinization, nuclear pleomorphism, number of mitoses per field , degree of invasion and tissue inflammation being classified into grade I, II and III. Immunostaining for COX-2 in actinic keratosis, carcinoma in situ and CSCC was evaluated considering distribution and intensity of staining, classified into scores (low and high immunoexpression). A total of 24 cats were included in this study, all mixed breed, 45.8% with white coat and 54.2% mixed, aged between 2 and 22 years (10.5 ± 4.6 years) with anatomical location 44 % in the nasal plane, 32% in the pinnae of the ears, 8% eyelids, 8% nasal plane and pinna, 4% in the pre-auricular region and 4% affecting the nasal plane with extension to the eyelid. Considering the histopathological classification, there were 2 cases of actinic keratosis, 1 of atypical epithelial hyperplasia, 3 of carcinoma in situ and 19 of invasive CSCC. Of these, 12/19 (63.2%) were classified as well differentiated and 7/19 (36.8%) as poorly differentiated. Nagamine's grading system allowed for the classification of 15.7% as grade I, 73.8% grade II and 10.5% grade III. Regarding the immunoexpression of COX-2, 10.5% of negative immunoexpression and 89.5% positive immunoexpression were observed, with 41.2 and 58.8% with low and high immunoexpression, respectively. The results indicate that there was a moderately significant correlation between the distribution of COX-2 marking and the mitotic index (p= 0.0387; rs=0.4772). Furthermore, it was observed that there was no significant correlation between the COX-2 immunoexpression score and clinical staging, histopathological Nagamine grade, disease-free interval or survival (ρ>0.05). Therefore, this study showed a high immunoexpression of COX-2 in feline CSCC, and that new studies, with a larger number of cases, and different ways of evaluating COX-2 expression can elucidate its prognostic importance.